The Performance Of Village Equipment In The Implementation Of The Service Of Uncertainty Letter (SKTM) In Pagar Dewa Village, Jarai District, Lahat District - Della Agusdianti Cipto; Amaludin Amaludin; Tri Rusilawati (Gayaku Publisher, 2023)
The purpose of this study was to determine the implementation of the SKTM (Certificate of Disadvantage) in Pagar Dewa Village, Jarai District, Lahat District. The administration of the activities of village officials is under the direction of a village management committee representing the central government. which is directly related to the communal village machine for village administration. Development of all fields Quantitative descriptive research method where the research objective is to describe events and phenomena in the field. The results showed that the government of Pagar Dewa Village, Jarai District, Lahat Regency, tried to improve services, firstly the education level of the workforce that would take care of the recruitment and placement of workers at the village office, secondly the facilities and infrastructure controlled by the Pagar Dewa Village village office, Jarai District, Lahat District. Third, officials must be given the most severe sanctions if they make mistakes or fail to fulfill the applicable provisions. The simplicity of service is very helpful for the community in this case because the service process is easy to understand and easy to implement without the impression of complicated service from local village officials.